سورۃ النبا کی ابتدائی آیات میں ذکر کردہ منتخب تقابلی مباحث(نبا عظیم اور عقیدہ آخرت ) کا علمی وتحقیقی جائزہ تفسیر حقانی کی روشنی میں: A Scholarly and Analytical Study of the Selected Comparative Discussions Mentioned in the Opening Verses of Surah Al-Naba (The Great News and the Belief in the Hereafter) in the Light of Tafsir Haqqani DOI:https://doi.org/10.5281/zenodo.16879836 DOI: https://doi.org/10.5281/zenodo.16879836 (Khairulummah, 2024)
The primary focus of these verses is to elucidate the reality of Qiyamah (Resurrection) and the Hereafter. Addressing those who reject the concept of divine recompense for human actions, the Qur’an delivers the momentous news of an inevitable day when the present world will cease to exist, humanity will be resurrected, and every individual will be rewarded or punished according to their deeds. For the insightful and reflective mind, this is indeed the Great News—a profound message that unsettles those who live without restraint, pursuing worldly desires, and believing that life ends with mere worldly existence.The disbelievers persistently, and with incredulity, questioned the Holy Prophet (ﷺ) regarding the timing and nature of that Day. These verses explore the varied modes of questioning and the diversity of opinions surrounding them. The exegeses of “An-Naba Al-‘Azim” are presented, incorporating the perspectives of renowned Mufassirun (Qur’anic commentators). The discussion further examines the positions of different religious traditions on the nature of the soul (ruh). In addition, the reasons behind the polytheists’ denial of the Hereafter are analyzed, shedding light on the intellectual and moral grounds for their rejection.
Keywords: Qiyamah, Hereafter, Reward , Punishment, Great News